Quantifying Corruption at a Subnational Level - Linhartová Veronika; Volejníková Jolana (My University, 2015)
Regarding the fact that bribery and other methods of corruption are illegal in most countries, their participants try to hide them very carefully and uncovering corruption is often almost impossible. Despite that a high number of specifi c procedures exist nowadays. A common feature of these methods is however that they focus on the corruption rate at the level of countries. Quantification of the corruption rate in smaller regional areas is still a considerably unexplored territory not only in the Czech Republic but also all over the world. Also the definition of the potential impacts of corruption or their precise quantifi cation is an area that was investigated only in general level of state. Detailed analysis of corruption still lacks regional dimension. Subnational distinction of a territory in terms of the corruption rate could provide a completely new extension of theories of reasons and consequences of regional disparities. There are several reasons why to focus on this issue. Perhaps the strongest reason is that if corruption is one of the variables that have an effect of reducing economic performance, the elimination of corruption in certain regions may be the key to the elimination of regional economic disparities and thus increase the economic performance of the state. The main goal of the presented article is formulated in this connection. It consists of a proposal of a methodology for quantifying the corruption rate in individual regions of the Czech Republic. It will be possible to mutually compare individual regions and at the same time define the rate of deviation of a region from “surface” corruption rate in a country. Definition of these regional disparities in corruption will be a benefi t mainly for anti-corruption policies of a country.
Kvantifikace korupce na subnacionální úrovni
Keywords: Corruption; region; regional disparities; Transparency International; Corruption Perception Index; Korupce; region; regionální disparity; Transparency International; Index vnímání korupce